2023
DOI: 10.2147/ott.s390458
|View full text |Cite
|
Sign up to set email alerts
|

A Refractory Case of CDKN2A/B Loss Metastatic Intrahepatic Cholangiocarcinoma Achieving a Partial Response After First-Line Treatment with Palbociclib

Abstract: Intrahepatic cholangiocarcinoma (ICC) is a highly aggressive and malignant subtype of biliary duct tumors. The poor prognosis of advanced ICC brings great challenges to clinical treatment, and chemotherapy-based therapy remains the standard first-line regimen. In recent years, the development of clinical research on targeted therapy for biliary duct tumors has brought new strategies for clinical treatment, but the targets are limited. Herein, we reported a 68-year-old patient with metastasis ICC harboring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The previous literature reported that the clinical trial of palbociclib monotherapy in patients with cholangiocarcinoma showed no response and poor efficacy, leading to the closure of the clinical trial ( 17 ). However, a successful case of PR has also been reported ( 18 ). Palbociclib can activate T cells, promote the immune system’s ability to kill tumor cells, and enhance the effectiveness of immunotherapy ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The previous literature reported that the clinical trial of palbociclib monotherapy in patients with cholangiocarcinoma showed no response and poor efficacy, leading to the closure of the clinical trial ( 17 ). However, a successful case of PR has also been reported ( 18 ). Palbociclib can activate T cells, promote the immune system’s ability to kill tumor cells, and enhance the effectiveness of immunotherapy ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 Multiple clinical studies showed benefit from CDK4/6 inhibitors in various cancers, and CDKN2A loss was found to have modest predictive value in few studies. 33 , 34 Loss of CDKN2A may contribute to tumorigenesis through dysregulation of the cyclin-dependent kinases and the cell cycle, and increased activity of CDK4 is a common event in sarcomas. Palbociclib showed antitumor activity in patients with STS with CDK4 amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot exclude the possibility of the observed response because of the antitumor effect of palbociclib, CDK4/6 inhibitors have shown modest benefit in various cancers harboring CDKN2A / B loss. 33 , 34 Therefore, it is likely that the combination of trametinib with palbociclib augmented the antitumor activities of both drugs or, less likely, that trametinib alone was solely responsible for the observed tumor regression. Indeed, previous studies have suggested tailoring treatments targeting as many alterations as possible is associated with better outcomes.…”
Section: Discussionmentioning
confidence: 99%